The Benefits Of Islamic Case Reflection In Medical Science Discipline On MPPD - Amalia Sri Anjani; Ida Royani; Nur Fadhillah Khalid (Sean Institute, 2024)
Reflection is an important method in medical education that has long been used to improve the quality of communication and learning. Reflection come from the Latin word reflectere, meaning “ to bend ” or “ to turn,” and refers to the process of self evaluation through reflection and analysis of experiences. Students with self reflection skills can develop into reflective practitioners. This lifelong learning process must be applied in medical education so that medical graduates can continue to apply it continuously in the health field. In medical education, the abilities to reflect not only increases the individual's capacity to act more effectively in similar situations in the future, but also help in the formation of a more balanced, calm, and objective professional attitude. Reflection and feedback is key elements in medical education because they support effective learning, the development of professional competence, and the formation of good attitudes and communication skills.